Ofdm-oqam as spectrum sensing technique (2012)
ABSTRACT: Spectrum sensing is a key function for the dynamic spectrum access. Filter bank-based multi-carrier communication techniques have been proposed as potential candidates for the physical layer of secondary users since can be used for both data communication and spectrum sensing with no additional cost. In this paper we evaluate one of these techniques, OFDM-OQAM, from the point of view of its misdetection probability as a function of the SNR and considering the multipath effect in the channel. It is showed that OFDM-OQAM outperforms the periodogram for low SNR values.